Ekonomi Sosial Masyarakat Nelayan Desa Bajo Kecamatan Sanana Utara Kabupaten Kepulaun Sula - Muhammad Kamal; Daud Hasyim; Musdar Muhammad (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to see the socio-economy of the fishing community of Bajo village, Sanan sub-district, Sula island district, Research using descriptive quantitative and qualitative methods, The data analysis technique used in this research is the analysis model developed by Miles and Huberman, namely analysis that uses three stages, namely data reduction, data presentation, and verification. The results of the research of the Bajo community have quite a lot of catches, but the costs of production costs are needed, and the results of enlargement are less targeted, as well as capital, fishing experience and age have a very important effect on increasing the income of Bajo village community fishermen. North Halmahera district, so that to meet the needs imported from other region.